1979
DOI: 10.1159/000122881
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Kinetic Studies and Inhibition by Oligopeptides of LH-RH Degradation in Rat Hypothalamus and Pituitary

Abstract: The enzyme kinetic parameters of the degradation of luteinizing hormone-releasing hormone (LH-RH) and L-cystine-bis-(4-nitroanilide) (Cys-NA) by rat hypothalamic (HYP) and pituitary (PIT) extracts and the effect of various oligopeptides on the rate of LH-RH inactivation were investigated in vitro. The 105,000 × g supernatant of 1 rat HYP inactivated 57 μg LH-RH during a 30 min incubation (Km = 12.4 μM,Vmax = 2.33 μg LH-RH/mg protein/min), and of one rat anterior PIT, 48 μg LH-RH during 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…One MBH fragment was incubated in 1 ml media for 2 h in the presence or absence of 6.7pgiml veratrine and then removed. Veratrine was then added to the control flasks, and GnRH peptidase activity and LDH activity were measured as described in can degrade GnRH faster than media containing an MBH, and (2) bacitracin, an antibiotic known to inhibit GnRH peptidases (McKelvy et al, 1976;Kuhl et al, 1979), can totally inhibit GnRH degradation during MBH incubations. The appearance of peptidase activity in the incubation media during MBH incubations was closely correlated with increases in the cytoplasmic enzyme LDH in the media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One MBH fragment was incubated in 1 ml media for 2 h in the presence or absence of 6.7pgiml veratrine and then removed. Veratrine was then added to the control flasks, and GnRH peptidase activity and LDH activity were measured as described in can degrade GnRH faster than media containing an MBH, and (2) bacitracin, an antibiotic known to inhibit GnRH peptidases (McKelvy et al, 1976;Kuhl et al, 1979), can totally inhibit GnRH degradation during MBH incubations. The appearance of peptidase activity in the incubation media during MBH incubations was closely correlated with increases in the cytoplasmic enzyme LDH in the media.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous groups have demonstrated that whole brain or hypothalamic homogenates contain peptidases capable of degrading GnRH as measured by a loss of biological activity, immunological activity, or amino acid release (Griffiths et al, 1973(Griffiths et al, , 1974Marks and Stern, 1974;Koch et al, 1974). A variety of other peptides and pnitroanilides and /3-naphthalamides of amino acids are cleaved by the peptidase degrading GnRH (Kuhl and Taubert, 1975;Reichlin, 1976;Kuhl et al, 1979). Bacitracin, a peptide antibiotic, can inhibit the peptidases degrading GnRH (McKelvy et al, 1976;Kuhl et al, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that LRH inhibits the cleavage of Cys-NA by hypothalamic and pitu¬ itary enzyme extracts and, vice versa, Cys-NA inhi¬ bits the degradation of LRH by the extracts (Kuhl &Taubert 1975a;Kuhl et al 1979). Previous experiments have also demonstrated that on isolated pituitary plasma membranes there is only a single type of LRH receptors with high affinity (Kd = 1.3 10"8 M) .…”
Section: Discussionmentioning
confidence: 99%
“…The arylamidase activity of the membrane suspension or of hypothalamic or pituitary extracts was determined as previously described (Kuhl & Taubert 1975a;Kuhl et al 1979). Incubations were carried out at a total volume of 2.5 ml at 37°C for a period of time of 30 min (Tris-HClbuffer 0.05 M, pH 7.4; lmM dithiothreitol; 0.1 mM Cys-NA).…”
Section: Assay Ofarylamidase Activitymentioning
confidence: 99%